UPAYA PEMENUHAN “NEED OF ACHIEVMENT” PADA REMAJA - Nasution, Ina Zainah; Sakinah, Nur; Husna, Asmaul (Berajah Journal, 2024)
Teenagers often have negative connotations. They are considered rebellious, fun-loving and irresponsible. But in reality, not all teenagers are like that. Many teenagers also have achievements. The need for achievement as part of psychological-sociological needs, if fulfilled, will bring balance and wholeness of personal integration; believe in yourself, value the strength, capability and feasibility of the individual concerned. It will also create inner harmony due to the fulfillment of self-esteem so that it can produce productive individuals. Fulfillment of achievement needs in adolescents is important to direct the lives of adolescents to be positive. Fulfillment of these achievement needs also requires efforts from within adolescents and support and reinforcement from the home and school environment.